O impacto inicial do laptop educacional no olhar de professores da rede pública de ensino - Silva, Renata Kelly da (2009)
This study aims to accomplish a comprehensive report of the first impressions of Basic Education teachers about the use of educational laptops in public school, those provided by the UCA Project (Um Computador por Aluno One Computer per Student) of the Federal Government and the Ministry of Education, as well as identifying the impact that this technology caused initially to those education professionals. The exploratory research, of qualitative nature, was performed with teacher of the Public School Network, within the facilities of the Catholic University of São Paulo (Pontifícia Universidade Católica de São Paulo PUC/SP). This environment was provided with wireless internet which enabled to analyze three prototypes of the educational laptop from different manufacturers. Since the workshop, there have been recorded the expectations and the initial impressions of the teachers before, during and after the contact with the educational laptop. The data obtained by the exploratory research was organized with extracts of depositions of the teachers at workshop extracted from the reflexive memorial and the answers of the questionnaires, being those last analyzed according to the methodology of the Collective Subject Speech (Discurso do Sujeito Coletivo DSC) through the software QualiQuantSoft. In research conducted a field observation work in a public school that uses the laptop education in the classroom. The analysis of the data collected in the workshop about the use of the educational laptop in the classroom presented queues of this being a technology different from those of the computing labs in the schools participant because it was mobile, reduced in size and wireless internet ready. After all the process of data analysis and the results exploration, I concluded that in the three research tools applied in the workshop, in the first moment, during the process, and at the end of the workshop, the category mobility and change in pedagogical practices were pointed out by the teachers in all times. Teachers demonstrated a good acceptance of this technology due to its pedagogical potential. At school, the use of educational laptop favored the relationship between teachers and students and students with students, respect and collaboration, that facilitated the involvement of students in the class and reinforces the results of the analysis